Exercise for Falls Prevention: Decision-making among Australian-born and Italian-born Older People - Liamputtong, P.; Lam, J.; Hill, Keith (Routledge, 2018)
© 2018, © 2018 Taylor & Francis Group, LLC. In this article, we examine factors contributing to decision-making in regards to participation and adherence to exercise to reduce falls by older people with recent falls history. Nineteen participants (9 Australian-born and 10 Italian-born; median age 78 years) who had =1 fall in the past 12 months and completed a community based physiotherapy program were recruited. Semi-structured interviews were conducted, transcribed, and thematically analyzed. The findings show that family, client-clinician relationship and personal experience affected decision-making and exercise participation. The findings revealed that a number of factors influenced older people’s decision and uptake of falls prevention exercise, including personal goals, recommendations from health care providers, and life experiences. There were some differences between the Italian-born and the Australian-born participants, including that most Australian-born participants adhere to exercise programs in order to avoid requiring nursing home care, whereas Italian-born individuals did not wish to be dependent on their children. An understanding of personal motivating and de-motivating factors for exercise for falls prevention are important for health and social care professionals to consider in engaging some groups of older people.